ANALISIS PROBLEMATIKA SISWA SMK DALAM MENYELESAIKAN SOAL SISTEM PERTIDAKSAMAAN LINEAR DUA VARIABEL - Waridah Waridah; Elsi Nulinda (AL KHAWARIZMI: Jurnal Pendidikan Matematika, 2026)
Mathematics is often used in everyday life, many people think mathematics is difficult, but there is actually no reason not to learn mathematics. From this assumption, a person, especially a student or student, is lazy to learn mathematics so that every time they encounter problems related to mathematics, they will have difficulties and encounter problems in solving them. One of the materials that students have problems with is the Two-Variable Linear Inequality System. This study aims to find out and analyze the problems experienced by high school students (SMK) class X in solving the problem of the Two-Variable Linear Inequality System. The results of the study show that some of the difficulties found are understanding the concept of inequality, determining the area of settlement, and interpreting the results in the form of graphs. By knowing the types of problems experienced by students, teachers can develop more effective and contextual learning strategies to improve students' understanding of the Two-Variable Linear Inequality System material.